Analysis of time series to examine the impact of the EU Timber Regulation (EUTR) on European timber trade - Georg Becher (Johann Heinrich von Thünen-Institut, 2019)
The objective of the EU Timber Regulation (EUTR), enforced since March 2013, is for importers and exporters to commit to reducing the risk of trading timber products from illegal sources in the EU. EUROSTAT time series on monthly trade with wood products from January 1988 to August 2016 were used to monitor the law's impact. The time series, subdivided into sections before and after the implementation of EUTR, were investigated in time and frequency domains. The analyses in the time domain indicated the adequateness of the AR (1) and ARMA (1, 1) models. As the confidence intervals for their estimates before and after EUTR do not overlap, the respective time series are considered as different and the influence of EUTR legislation probable (also confirmed by the significant models with EUTR as intervening event). Long term variation of the monthly time series (March 2013 to August 2016) show an increasing linear trend for all wood products and for wood products with tropical woods excluded. Since EU imports of tropical wood were falling before EUTR, the stagnant imports thereafter are judged as uncertainty and time the markets need to adapt to a new legislative situation. The analyses in frequency domain based on inference from periodogram revealed cycles of 3, 4, 6 and 12 months, except for time series of tropical wood imports after EUTR. If cycles are thought of as inherent to import time series, this lack in tropical wood imports can be an indication of a 'wait-and-see' attitude of importers as a consequence of EUTR. – – Die Europäische Holzhandelsverordnung (EUTR) trat im März 2013 in Kraft. Diese Verordnung zielt darauf ab, die Verpflichtung der Marktteilnehmer in der EU zur Vermeidung des Holzhandels aus illegalen Quellen zu stärken. Um die Auswirkungen von EUTR auf Holzhandel zwischen Europa und nichteuropäischen Ländern bewerten zu können, wurden, auf EUROSTAT Daten basierend, umfangreiche Zeitreihenanalysen für den Zeitraum vom Januar 1988 bis August 2016 durchgeführt. Die Zeitreihen wurden sowohl im Zeit- als auch im Frequenzbereich untersucht. Dabei zeigte sich, dass zur mathematisch-statistischen Modellierung der monatlichen Handelsmengen mit Holzprodukten autoregressive AR(1) bzw. Autoregressiv-Moving-Average Modelle ARMA(1, 1) adäquat sind. Die Analyse der partitionierten Abschnitte der Zeitreihen vor und nach Inkrafttreten der EUTR ergab statistisch signifikante Unterschiede, so dass der Einfluss der Holzhandelsverordnung als Interventionseffekt im Holzhandel als wahrscheinlich erachtet wird. Wichtig ist allerdings, dass der Holzhandel wegen EUTR keine quantitativen Einbrüche verzeichnet: der Handel mit allen Holzprodukten weist sogar einen positiven, linearen Trend ab März 2013. Da die Importe der tropischen Holzprodukte vor dem Inkrafttreten der EUTR rückläufig waren, kann die Stagnation des Holzhandels mit den tropischen Holzprodukten nach EUTR auf eine Unsicherheit der Marktteilnehmer und eine Art von 'wait-and-see' Verhalten hindeuten. Festgestellt wurde auch eine auffällige Veränderung der Zeitreihen im Frequenzbereich: die vor EUTR deutliche 3, 4, 6 und 12 monatliche Zyklen bei Importmengen aus den tropischen Ländern konnten in den Zeitreihen nach Inkrafttreten der EUTR nicht mehr nachgewiesen werden.
urn:nbn:de:gbv:253-201911-dn061650-1
Keywords: 630; illegale Holznutzung; Zeitreihenanalyse; Interventionsmodell; illegal logging; time series analysis; periodogram; intervention model